Dissolved Inorganic Carbon Pump in Methane-Charged Shallow Marine Sediments: State of the Art and New Model Perspectives - Akam, Sajjad A.; Coffin, Richard B.; Abdulla, Hussain A. N.; Lyons, Timothy W. (Frontiers in Marine Science, 2020)
Methane transport from subsurface reservoirs to shallow marine sediment is characterized by unique biogeochemical interactions significant for ocean chemistry. Sulfate-Methane Transition Zone (SMTZ) is an important diagenetic front in the sediment column that quantitatively consumes the diffusive methane fluxes from deep methanogenic sources toward shallow marine sediments via sulfate-driven anaerobic oxidation of methane (AOM). Recent global compilation from diffusion-controlled marine settings suggests methane from below and sulfate from above fluxing into the SMTZ at an estimated rate of 3.8 Tmol yr-1 and 5.3 Tmol yr-1 respectively, and wider estimate for methane flux ranges from 1—19 Tmol yr-1. AOM converts the methane carbon to dissolved inorganic carbon (DIC) at the SMTZ. Organoclastic sulfate reduction (OSR) and deep-DIC fluxes from methanogenic zones contribute additional DIC to the shallow sediments. Here, we provide a quantification of 8.7 Tmol yr-1 DIC entering the methane-charged shallow sediments due to AOM, OSR, and the deep-DIC flux (range 6.4–10.2 Tmol yr-1). Of this total DIC pool, an estimated 6.5 Tmol yr-1 flows toward the water column (range: 3.2–9.2 Tmol yr-1), and 1.7 Tmol yr-1 enters the authigenic carbonate phases (range: 0.6–3.6 Tmol yr-1). This summary highlights that carbonate authigenesis in settings dominated by diffusive methane fluxes is a significant component of marine carbon burial, comparable to ~15% of carbonate accumulation on continental shelves and in the abyssal ocean, respectively. Further, the DIC outflux through the SMTZ is comparable to ~20% of global riverine DIC flux to oceans. This DIC outflux will contribute alkalinity or CO2 in different proportions to the water column, depending on the rates of authigenic carbonate precipitation and sulfide oxidation and will significantly impact ocean chemistry and potentially atmospheric CO2. Settings with substantial carbonate precipitation and sulfide oxidation at present are contributing CO2 and thus to ocean acidification. Our synthesis emphasizes the importance of SMTZ as not only a methane sink but also an important diagenetic front for global DIC cycling. We further underscore the need to incorporate a DIC pump in methane-charged shallow marine sediments to models for coastal and geologic carbon cycling.